PROTEOMIC PROFILING OF CARALLUMA FIMBRIATA CELL WALL DURING DROUGHT CONDITION - SONALI P. PATIL; ABHAY N. SALVE; VIJAY B. BALADHYE (International Journal of Pharma and Bio Sciences, 2013)
Water is one of the vital components of all living beings that triggered several biochemical changes by adding or withdrawal. Inside plants several oxidative injuries at the cellular level occurs as a result of water stress or other stresses. At cellular level, cell wall is one of the important components of plant cell that protect, support and involved in maintaining the permeability, integrity and physiological conditions inside the cell. In the present study we have applied expressional proteomic approach to find out up or down regulated cell wall proteins during drought condition. The immature plants of Caralluma fimbriata were used as a model organism and grown with water and without water up to their mature stage. Shoot parts of both plants were collected, homogenized, fractionated and cell wall fraction and their proteins were isolated with the help of standard biochemical techniques. The result obtained from these techniques clearly indicates that the basic proteins of water stress condition were induced than control. All these up-regulated basic proteins involved in transport and maintaining integrity during drought. So this type of approach can be extremely resourceful to interpret various growth conditions and it can be used as a prefractionation approach in proteome analyses.